How to review online an OBJN article - Isabel C.F. da Cruz (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2005)
Automated manuscript revision permits publish faster and improve focus on content. This article guides reviewers' online analysis of manuscript.